Being funny is not enough: the influence of perceived humor and negative emotional reactions on brand attitudes. Issue 7 (3rd October 2019) - Warren, Caleb; Carter, Erin Percival; McGraw, A. Peter
Abstract: Humor is a common goal of marketing communications, yet humorous advertisements do not always improve consumer attitudes towards the advertised brand. By investigating a potential downside of attempting to be humorous, our inquiry helps explain why humorous ads can fail to improve and potentially even hurt, brand attitudes. We show that advertisements intended to be humorous also risk causing negative emotions independent of humor appreciation. We investigate the link between humor appreciation, negative emotional reactions and brand attitudes using four samples of advertisements. We find that attitudes towards an advertised brand depend less on the degree to which the ad seems funny and more on the degree to which the ad triggers negative emotional reactions. Consequently, whether an advertisement helps or hurts brand attitudes depends on whether the ad decreases or increases consumers' negative feelings independent of perceived humor.